Kajian Feminisme Dalam Kumpulan Cerpen “Akar Pule” Karya Oka Rusmini - Astuti, Ni Made Ignityas Prima; Dewi, Made Sri Astika (Indonesian Research Journal on Education, 2022)
The research aim is to know the gender injustice in the form of violence, affair, stereotype, and theworkload experiences by female characters whether in the family nor in society which contains in Akar Pule Short Story Collection. The method used in this research is descriptive qualitative. The data source is from Akar Pule Short Story Collection by Oka Rusmini published in 2012. This research used documentation method which used document recording technique from the quotes of Akar Pule Short Story Collection by Oka Rusmini. In this short story collection, it discusses women with Balinese cultural background. As a shortstory collection, Akar Pule presents a variety of stories with a distinctive plot, however it still refers to the thematic and women’s point of view. Oka Rusmini plays role in several of social and cultural cases. Whether it is a woman with caste issues and strange customs, a woman with her injustice and a love history. Through the research of feminism, the results obtains of nine forms which quotes about gender injustice violence, nine quotes about affair, seven quotes about stereotype, and three quotes about the workload of female characters in Akar Pule short story collection.